Video self instruction method to improve self esteem - Febriyani, Tika; Mawarni, Anisa; Subandi, Subandi (KONSELI: Jurnal Bimbingan dan Konseling (E-Journal), 2022)
Self-esteem ability is really needed based on the data from the distribution of the instrument, there are 61.6% of students who do not love themselves and have low self-esteem abilities and 90.4% feel the need for efforts to increase self-esteem abilities The aim of this study was to produce a method of counseling services that can increase individual self-esteem. This research used research and development methods or "Research and Development" (R&D). The population of this study was the students of UIN Raden Intan Lampung. This study used descriptive data analysis techniques. The findings were the video self-instruction method could increase self-esteem with the results of the content expert test with a score of 4.875 and it implied that it was "very feasible" and the media expert test with a score of 4.625 implied "very feasible" and the validity test could increase self-esteem by 48 ,75%. In conclusion, the video self-instruction method could be used by counselors to increase self-esteem in providing guidance and counseling services both face-to-face and bravely so as to simplify and improve service quality.